Sosialisasi Pemanfaatan Lahan Sempit untuk Budidaya Sayuran Vertikultur - Victor Bintang Panunggul; Sitanini, Ayu; Putranto, Afif Hendri; Susanto, Niken Hapsari Arimurti (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2025)
The community service aims to improve the utilisation of narrow land through vegetable cultivation. Creativity in utilising existing space becomes very important in the context of increasing urbanisation. In this effort, people were given training and socialisation on effective and environmentally friendly farming methods. The results of the community service that includes the use of narrow land for vegetable cultivation show that these efforts have great potential to improve food security and community welfare. The liquid organic fertiliser produced from this fermentation not only provides nutrients for plants, but also improves soil health and supports ecosystem sustainability. The enthusiasm and liveliness of the participants is good and it is hoped that they can implement narrow land around the house and can increase income, and improve the environment through this community service programme.